Pengaruh Budaya Kerja, Motivasi Kerja dan Pelatihan Kerja terhadap Kinerja Karyawan CV Green Riverina Demeling Jepara Jawa Tengah - Roghibun Ainun Mahfud; Stefanus Sri Sadana; Siti Safaria (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2023)
The purpose of this study is to obtain empirical evidence and analyze the factors affecting employee performance. Independent variables in this study are work culture, work motivation, job training. While the dependent variable in this study is employee performance. The company used in this study is a company engaged in furniture export called CV Green Riverina. The total sample in this study was 58 employees of CV Green Riverina. This study used the multiple linear regression method to examine the influence of independent variables on dependent variables. The results showed that work culture variables have a positive and significant effect on employee performance, Work Motivation has no effect on employee performance, while job training has a positive and significant effect on employee performance. Adjusted R Square of 0.459 which means that employee performance is influenced by work culture, work motivation, job training with a percentage of 45.9% and the remaining 54.1% is influenced by other factors.